ANALISIS PENGARUH PERSEPSI HARGA, LOKASI PELANGGAN, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Super Sambel Semarang Cabang Lamper) - Pudji Utomo, Danang; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2018)
The rapid development of the culinary business in the city of Semarang is also supported by consumer behavior itself. Family cities tend to be practical, they choose instant food and liked the restaurant with atmosphere